Interaction mechanism of hausmannite and Mn2+ under oxic conditions: Catalytic oxidation of Mn2+ to low-valence manganese oxides and mineral phase transformation. (October 2022) - Luo, Yao; Wang, Yi; Liu, Lihu; Yang, Xiong; Wang, Li; Qiu, Guohong
Abstract: Hausmannite is a common and widely distributed low-valence manganese oxide in soils and sediments. The transformation of this metastable mineral greatly influences the toxicity and geochemical cycling of trace elements. Mn 2+ aq can be adsorbed and oxidized by Mn(III)/Mn(IV) oxides and influences the transformation of these minerals, while little attention has been paid on the interaction between Mn 2+ aq and hausmannite. Here, the interaction process of Mn 2+ aq and hausmannite under oxic conditions and the influence of pH, Mn 2+ aq concentration and oxygen were systematically investigated. Hausmannite was progressively oxidized to manganite in the single hausmannite system. After the addition of Mn 2+ aq, adsorbed Mn 2+ can be slowly catalytically oxidized to manganite by hausmannite and the transformation rate of hausmannite to manganite decreased under oxic conditions. The oxidation rate of Mn 2+ aq increased with increasing oxygen partial pressure. The generation rate of manganite was the lowest under neutral pH conditions in the reaction system of Mn 2+ aq and hausmannite. Both hausmannite dissolution at acidic pH and adsorbed Mn 2+ oxidation at alkaline pH facilitated manganite formation. These findings improve our understanding of the formation and transformation of low-valence manganese oxides in natural environments. Graphical abstract: Adsorbed Mn 2+ is oxidized to manganite on hauamannite surface in air atmosphere. The transformation of hausmannite to manganite is inhibited by the presence of Mn 2+ aq and both acidic and alkaline pH facilitate the formation of manganite. Image 1 Highlights: Mn 2+ aq is catalytically oxidized to manganite on hausmannite surface by oxygen. Manganite formation rate is the lowest from hausmannite reacting with Mn 2+ at pH 7. Mn 2+ catalytic oxidation rate by hausmannite is lower than that by manganite.